ANALISIS PERFORMANSI ANTENA YAGI-UDA 11 ELEMEN SEBAGAI PENGUAT SINYAL GLOBAL SYSTEM FOR MOBILE COMMUNICATION (GSM) - Abdurrahman, Tanridio Silviati Delfina; Saad, Andi Muhammad; Bulgis, Bulgis (PROtek : Jurnal Ilmiah Teknik Elektro, 2018)
Limited telecommunication network services, even for 2G technology, in some regions due to living in small islands, range of hills and blank spot areas are experienced in Indonesian Republic. One of solutions is proposed by using 11-element Yagi-Uda antenna operated in GSM band of frequencies. Mmanagal software is run to simulate this proposed model in order to analyze antenna performance parameters namely field pattern, F/B ratio, gain antenna, input impedance and SWR. First of all, the antenna performance, operated at frequency of 925 MHz, is the best because of the ideal SWR. Furthermore, the performance parameters of the antenna at GSM’s uplink frequency, 902.5 MHz, are good because the SWR value is less than 2 dB. However, drawback of the antenna performance is occurred in which the model antenna is operated at central frequency of GSM downlink, 947.5 MHz. It is stated that radiated pattern, back lobe is more dominant than main lobe, is vice versa with two other operated frequencies. Moreover, the value of SWR, slightly above 4.6 dB, is more than 2 dB.